Olfactory bulb magnetic resonance imaging in SARS-CoV-2-induced anosmia in pediatric cases. (December 2020) - Hatipoglu, Nevin; Yazici, Zahide Mine; Palabiyik, Figen; Gulustan, Filiz; Sayin, Ibrahim
Abstract: In this paper, we report three cases of pediatric patients with COVID-19 infection who presented with different symptoms and also anosmia and/or ageusia. The common feature of these 3 patients is that the smell and / or taste disorder developed without nasal symptoms such as nasal congestion, nasal obstruction or rhinorrhea. Although 40% of anosmies contains viral etiologies, COVID- 19 differs from other viral anosmies by the lack of nasal congestion and runny nose. Coronaviruses could invade the brain via the cribriform plate close to the olfactory bulb and the olfactory epithelium. We may expect some structural changes in the olfactory bulb so we evaluated our patient with cranial imaging.